Relapse of Visceral Leishmaniasis in an HIV-Infected Patient Successfully Treated with a Combination of Miltefosine and Amphotericin B. Issue 6 (2015) - McQuarrie, Shauna; Kasper, Ken; Moffatt, Dana C; Marko, Daniel; Keynan, Yoav
Abstract : The present report documents a 49-year-old HIV-infected man receiving antiretroviral therapy with a suboptimal immune response and a CD4 count of 95 cells/mm 3, despite virological suppression. Investigation of bone marrow was conducted and yielded a diagnosis of visceral leishmaniasis. The clinical course was complicated by gastrointestinal involvment and relapse occurred after amphotericin B therapy. With the addition of miltefosine, the patient no longer presented with bone marrow amastigotes, and displayed an increased CD4 count and negative Leishmania polymerase chain reaction results. The present case highlights atypical presentation of visceral leishmaniasis, including poor immune reconstitution and gastrointestinal involvement. The high likelihood of relapse and response to combination therapy are illustrated.